Analisis Kebijakan Program Ekoteologi UIN Sulthan Thaha Saifuddin Jambi: Tantangan Kurikulum dan Sinergi - Risye Martarika (JURNAL ILMIAH GEMA PERENCANA, 2025)
This policy article is motivated by the unsuccessful implementation of the Ministry of Religious Affairs' ecotheology priority program at UIN Sulthan Thaha Saifuddin Jambi. A gap exists between the program's ideal goal of producing relevant graduates and the reality on the ground, where curriculum implementation has not been effectively integrated with the real needs of the local community and industry, and weak synergy between stakeholders. The methodology of this paper uses a qualitative approach with a descriptive analysis approach, case study and Urgency, Seriousness, Growth (USG) analysis and William N. Dunn's theory. The results of the paper indicate that "Lack of Curriculum Relevance" is the most prioritized problem with a total score of 14. The root of the problem is the limited understanding and awareness of UIN Sulthan Thaha Saifuddin Jambi's internal stakeholders regarding the urgency of curriculum renewal. The most effective policy alternative is "Partnership-Based Curriculum Revision" with a score of 21. The Conclusion and Recommendations of this paper recommend the issuance of a Rector's Circular to issue a Partnership-Based Ecotheology Program Curriculum Revision involving academics, practitioners, industry, and local governments to ensure graduates have competencies relevant to contemporary environmental challenges